Rancangan Program Robotika Marsheller di Akademi Teknik dan Keselamatan Penerbangan Makassar - Indrawan, Indrawan; Prihatin, Rudy; Ode Muhammad Makmun, La (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2018)
Aerodrome plays the role as the node movement of aircraft which needs a various kind of facility and infrastucture’s contributor for the aviation operational’s flowliness based on regulation and provision which is listed on annex 14 telling about aerodrome. Apron is facility in aerodrome that has a lot of function such as for the aircraft parking, loading/unloading the passangger and stuff, and movement intra and antarmoda transportation. Qualified human resources are needed in order to be able to handle the aircraft on the apron so that movement’s activity would be efficient and effective. Civil Aviation Safety and Engginering of Academi (CASEA) Makassar opens Marshalling shortcourse program to produce human resource which is wanted by Ministry fof Transportation. The objective of this design was producing robotic marshaller’s design for guidance of aircraft’s parking as the learning media to easify the student of marshalling shortcourse CASEA Makassar on process to park the aircraft to parking stand until it stops. This design was application of Arduino Mega 2560 to produe narshaller activity’s simulation for aiecraft’s parking guidance in accordance with Annex 2 telling about Rule of the air. The result of this design was to give an understandable perspective for the shortcourse’s student instead of using material which was written down on whiteboard or slide in powerpoint. Besides that, this simulation’s persepetive can be seen from various aircraft’s position, marshaller and the sign on airport simultaneously. So by using this design, CASEA MAKASSAR can improve the quality of the marshalling shortourse’s student.